Efficacy of dexmedetomidine for the control of junctional ectopic tachycardia after repair of tetralogy of Fallot - Rajput, Randhir S (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Junctional ectopic tachycardia occurs frequently after congenital cardiac surgery and can be a cause of increased morbidity and mortality. Dexmedetomidine (DEX) is an α2 adrenoreceptor agonist, has properties of controlling tachyarrhythmia by regulating the sympatho-adrenal system. OBJECTIVE: To evaluate the efficacy of DEX for control of junctional ectopic tachycardia after repair of Tetralogy of Fallot (TOF). MATERIALS AND METHODS: Two hundred and twenty pediatric cardiac patients with TOFs were enrolled in a prospective randomized control study. Patients underwent correction surgery. They were divided into two groups, i.e., Group 1 (DEX) and Group 2 (control). Heart rate, rhythm, mean arterial pressure (MAP) were recorded after the anesthetic induction (T1), after termination of bypass (T2), after 04 hours (T3), and 08 hours after transferring the patient to intensive care unit (ICU; T4). RESULTS: Heart rate was comparable between two groups before starting the drug but statistically significant after bypass until 08 hours after transferring the patient to ICU. Junctional ectopic tachycardia occurred more in Group-2 (20%) as compared to Group-1 (9.09%; P = 0.022). Junctional ectopic tachycardia occurs early in Group-2 (0.14 ± 0.527 hours) as compared to Group 1 (0.31 ± 1.29 hours; P = 0.042). The duration of junctional ectopic tachycardia was more prolonged in Group-2 (1.63 ± 3.64 hours) as compared to Group-1 (0.382 ± 1.60 hours; P = 0.012). The time to withdraw from mechanical ventilation and ICU stay of Group 1 patient was less than of Group 2 patients (P = <0.001). CONCLUSION: DEX had a therapeutic role in the prevention of junctional ectopic tachycardia in patients undergoing repair for TOF.